2016
DOI: 10.1177/1077801216656828
|View full text |Cite
|
Sign up to set email alerts
|

Calling the Shots: How Family Courts Address the Firearms Ban in Protection Orders

Abstract: Access to firearms increases the risk of a batterer killing his partner. Moreover, firearms may be more common in homes where intimate partner abuse has occurred. The Violence Against Women Act of 1994 banned possession of firearms by individuals subject to civil protection orders. Yet little research has focused on how this ban is communicated to survivors and batterers. Drawing on systematic observations of protection order hearings, the current study explores factors related to judicial discussion of the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Unlike Vittes and Sorenson's (2006) assessment of PO granting overall, when it comes to firearm removal clauses severity of abuse and gun ownership were significant predictors of granting removal. Prior qualitative studies have found that firearm removal is irregularly implemented ) and inconsistently communicated to petitioners (Fleury-Steiner et al 2017;Webster et al 2010), and this quantitative study finds similar rates of issuance.…”
Section: Discussionsupporting
confidence: 58%
“…Unlike Vittes and Sorenson's (2006) assessment of PO granting overall, when it comes to firearm removal clauses severity of abuse and gun ownership were significant predictors of granting removal. Prior qualitative studies have found that firearm removal is irregularly implemented ) and inconsistently communicated to petitioners (Fleury-Steiner et al 2017;Webster et al 2010), and this quantitative study finds similar rates of issuance.…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, a strong gun culture is also pervasive in rural communities outside Appalachia. Further, the consistency of firearm confiscation in domestic violence cases is inconsistent and problematic even in states that possess domestic violence firearm laws (Fleury‐Steiner et al ). Therefore, the results may be used to guide both research and policy implementation in other states across the United States.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all states possess statutes that prohibit protective order respondents from possessing a firearm. In fact, little is known regarding the implementation and consistency of the enforcement of mandated gun‐confiscation procedures (Fleury‐Steiner, Miller, and Carcirieri )—particularly at the community level in states that lack uniform statewide gun laws.…”
Section: Domestic Violence Gun Control Policymentioning
confidence: 99%
“…Fleury-Steiner, Miller, and Carcirieri (2017) found that judges do not always let domestic violence victims know of their rights to have firearms removed during a protection order (Fleury-Steiner et al, 2017). In the Delaware court she and her colleagues observed, over a quarter of judges did not mention to the victim of the firearm dispossession laws (Fleury-Steiner et al, 2017). They argue that this negligence in failing to inform of a firearm dispossession law can put many women in harm's way (Fleury-Steiner et al, 2017).…”
Section: Judicial and Law Enforcement Discretion On Firearm Dispossesmentioning
confidence: 99%
“…In the Delaware court she and her colleagues observed, over a quarter of judges did not mention to the victim of the firearm dispossession laws (Fleury-Steiner et al, 2017). They argue that this negligence in failing to inform of a firearm dispossession law can put many women in harm's way (Fleury-Steiner et al, 2017). Knowing about firearm dispossession laws, such as ERPOs, is dependent upon law enforcement and judges to inform individuals of their choices.…”
Section: Judicial and Law Enforcement Discretion On Firearm Dispossesmentioning
confidence: 99%